2020
DOI: 10.1007/978-3-030-45771-6_26
|View full text |Cite
|
Sign up to set email alerts
|

The Integrality Number of an Integer Program

Abstract: We introduce the integrality number of an integer program (IP) in inequality form. Roughly speaking, the integrality number is the smallest number of integer constraints needed to solve an IP via a mixed integer (MIP) relaxation. One notable property of this number is its invariance under unimodular transformations of the constraint matrix. Considering the largest minor ∆ of the constraint matrix, our analysis allows us to make statements of the following form: there exist numbers τ (∆) and κ(∆) such that an I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…, ∆}. In view of other work on linear and integer programs with bounded subdeterminants [42,44,3,11,13,34], it is tempting to believe that integer programs defined by totally ∆-modular matrices can be solved in polynomial time whenever ∆ is a constant. While this question is still open (even for ∆ = 3), we prove the following result.…”
Section: Introductionmentioning
confidence: 99%
“…, ∆}. In view of other work on linear and integer programs with bounded subdeterminants [42,44,3,11,13,34], it is tempting to believe that integer programs defined by totally ∆-modular matrices can be solved in polynomial time whenever ∆ is a constant. While this question is still open (even for ∆ = 3), we prove the following result.…”
Section: Introductionmentioning
confidence: 99%
“…Our final approximate result, which we prove at the end of Section 8, can be used to show that certain integer programs can be solved efficiently; see [34] and [17] for a detailed discussion. Given a positive integer ∆, we say that an integer matrix A is ∆-modular if the determinant of each rank(A) × rank(A) submatrix has absolute value at most ∆.…”
Section: Corollariesmentioning
confidence: 89%
“…In 2009, Veselov and Chirkov showed that the feasibility problem can be solved in polynomial time when ∆ = 2 [102], and the optimization version was resolved using deep techniques from combinatorial optimization by Artmann, Weismantel and Zenkulsen in [5]. See also related results for general ∆ in [4,12,[57][58][59]89].…”
Section: Mixedmentioning
confidence: 99%